Rancang Bangun Aplikasi Digistun sebagai Upaya Pencegahan Stunting di Desa Babakanjati - Ripki Ramdani; Hana Astria Nur; Yogi Nugraha (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
Nutritional problems in toddlers are still a major problem in the population order. Nutritional problems in toddlers include stunting and wasting. The digistun application is an integral part of everyday life, and its use as a medium to improve healthy behavior in preventing stunting. This service aims to help prevent stunting through internet technology in increasing awareness and understanding of parenting patterns in preventing stunting. Based on the results of this community service activity, it was concluded that the digistun application can be an effective means of increasing knowledge about proper nutrition and a balanced diet. It can be concluded that the digistun application has great potential in improving healthy community behavior in preventing stunting. With the right approach and development of user-friendly applications, the digistun application can be an effective tool in supporting nutrition education, promoting a balanced diet, and a healthy lifestyle in general. Collaborative efforts between the government, health institutions, the world of education, and the private sector are very important to maximize the positive impact of utilizing the digistun application in preventing stunting and reaching a healthier future generation..